2013
DOI: 10.1155/2013/793819
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative Localization and Surgical Margins in Conservative Breast Surgery

Abstract: Breast-conserving surgery (BCS) is the treatment of choice for early breast cancer. The adequacy of surgical margins (SM) is a crucial issue for adjusting the volume of excision and for avoiding local recurrences, although the precise definition of an adequate margins width remains controversial. Moreover, other factors such as the biological behaviour of the tumor and subsequent proper systemic therapies may influence the local recurrence rate (LRR). However, a successful BCS requires preoperative localizatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
59
3
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(69 citation statements)
references
References 74 publications
(118 reference statements)
1
59
3
4
Order By: Relevance
“…Studies have shown that clear margins are obtained in 90-92% of excisional specimens when lesions are localized using biopsy markers vs 31-62% when wire localization is used alone. 2,3 A well-known complication of marker use is the immediate displacement from the biopsied lesion. Most cases of displacement are believed to be caused by the so-called "accordion effect".…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that clear margins are obtained in 90-92% of excisional specimens when lesions are localized using biopsy markers vs 31-62% when wire localization is used alone. 2,3 A well-known complication of marker use is the immediate displacement from the biopsied lesion. Most cases of displacement are believed to be caused by the so-called "accordion effect".…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the US visibility of TCC allows a precise localization of the lesion, since the patient is supine with the upper limb adducted thus the breast position is the same as in the operating room. Conversely, localization methods based on mammographic guidance such as WGL, might be less accurate and more difficult because the patient need to stand in upright position, thus the breast is in a different position, and measurements between the lesion and the nipple‐areola complex or radiopaque metallic marker on the skin are required . Another advantage offered by TCC is their wide usefulness beyond surgical needs.…”
Section: Discussionmentioning
confidence: 99%
“…Breast-screening US has increased the detection rate of nonpalpable breast cancer, and BCS has become the treatment of choice for early breast cancer (7,8). Adequate preoperative localization is very important for the successful and minimal excision of a nonpalpable breast lesion.…”
Section: Discussionmentioning
confidence: 99%
“…Adequate preoperative localization is very important for the successful and minimal excision of a nonpalpable breast lesion. Several procedures such as wire-guided localization, radioisotope localization, dye injection (toluidine blue or methylene blue), and charcoal marking have been used to localize nonpalpable breast lesions (7)(8)(9)(10). Compared to other procedures, charcoal marking avoids the risk of displacement and can thus be used with delayed surgeries (7).…”
Section: Discussionmentioning
confidence: 99%